Self-perceived neighborhood factors and OHRQoL among adolescents: a population-based study in southern Brazil - Ângela DALLA NORA; Jéssica Klöckner KNORST; Letícia Donato COMIM; Débora Nunes de Oliveira RACKI; Luana Severo ALVES; Júlio Eduardo do Amaral ZENKNER (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study aimed to assess the relationship between self-perceived neighborhood factors and oral health-related quality of life (OHRQoL) among adolescents from southern Brazil. A representative sample of 15-19-year-old students from Santa Maria, Brazil, was included. The Oral Health Impact Profile (OHIP-14) was used to assess the OHRQoL. Self-perceived neighborhood factors were assessed through a structured questionnaire and included characteristics of the neighborhood where the adolescents lived, such as the presence of paved streets, tap water, community social networks, and availability of dental services and the Family Health Strategy (FHS). In addition, socioeconomic, behavioral, and clinical variables (dental caries and malocclusion) were also evaluated. Multilevel Poisson regression analysis with a hierarchical approach was used to assess the association between predictors and OHIP-14. The rate ratio (RR) and 95% confidence intervals (CIs) were estimated. A total of 1,197 adolescents were included in this study (participation rate: 72.3%). The mean OHIP-14 score was 8.4 (standard error = 0.2), ranging from 0 to 49. Living in residences with unpaved streets (RR = 1.11, 95%CI:1.06−1.17), no tap water (RR = 1.11, 95%CI: 1.02−1.20), absence of the FHS services (RR = 1.15, 95%CI: 1.09−1.20), and the availability of dental services (RR = 1.08, 95%CI: 1.03−1.14) were associated with higher OHIP-14 scores, indicating a poorer OHRQoL. In addition, lower socioeconomic status, visiting the dentist for curative reasons, lower frequency of brushing teeth, and higher sugar consumption were also associated with higher OHIP-14 scores. In conclusion, self-perceived neighborhood characteristics were associated with OHRQoL in adolescents. Adolescents who perceived their neighborhood as deprived had poorer OHRQoL.